(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the clinical and ultrasound imaging characteristics of patent processus vaginalis (PPV) in children and to analyze the value of ultrasound in diagnosing PPV in children. Subjects and Methods: All patients aged ≤16 years diagnosed with PPV by ultrasound and surgery at Nghe An Obstetrics and Pediatrics Hospital were included. The study was designed as a retrospective, descriptive, and analytical study, with a comparative analysis of 234 eligible patients. Results: The average age was 3.6 ± 2.3 years, with a male-to-female ratio of 5,4/1. Disease duration of 1–6 months accounted for 50.6% of cases. The main reason for hospital admission was groin swelling or scrotal/labial swelling, observed in 93.4% of cases. Herniated contents were primarily bowel loops, accounting for 64.8%. The highest rate of incarcerated inguinal hernia was associated with ovarian herniation, accounting for 25%. All cases of incarcerated inguinal hernia showed no Doppler signal. Conclusions: The average sac diameter correlated with the type of hernia. Ultrasound is a simple, inexpensive, and highly valuable first-line diagnostic tool for PPV in children.